2011
DOI: 10.1007/978-3-642-19595-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Locality Optimization of Stencil Applications Using Data Dependency Graphs

Abstract: Abstract. This paper proposes tiling techniques based on data dependencies and not in code structure. The work presented here leverages and expands previous work by the authors in the domain of non traditional tiling for parallel applications. The main contributions of this paper are: (1) A formal description of tiling from the point of view of the data produced and not from the source code. (2) A mathematical proof for an optimum tiling in terms of maximum reuse for stencil applications, addressing the dispar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…In our second study [17], we found that there is a high similarity in tasks from the same actor: They have the same properties and they execute the same function. Such similarity can be exploited to decrease the number of operations required to write those tasks in the centralized queue, greatly reducing the overhead of the runtime system.…”
Section: Runtime Systemmentioning
confidence: 70%
See 3 more Smart Citations
“…In our second study [17], we found that there is a high similarity in tasks from the same actor: They have the same properties and they execute the same function. Such similarity can be exploited to decrease the number of operations required to write those tasks in the centralized queue, greatly reducing the overhead of the runtime system.…”
Section: Runtime Systemmentioning
confidence: 70%
“…The implementation of TIDeFlow presented several challenges that ultimately resulted in interesting advances and tools: A fully distributed runtime system, a programming language to describe program graphs, concurrent algorithms [17] and new ways to reason about performance models [18].…”
Section: Implementation Of Tideflowmentioning
confidence: 99%
See 2 more Smart Citations
“…Several applications were tested: Fast Fourier Transforms that use the CooleyTukey algorithm with two-point butterflies (FFT) and simulations of electromagnetic waves propagating using the Finite Difference Time Domain algorithm in 1 Dimension (FDTD1D) [15] and 2 dimensions (FDTD2D) [14]. FFT was run with input sizes 2 9 (FFT2P 2 9 ) through 2 12 (FFT2P 2 12 ), FDTD1D runs a problem of size 20000 with 3 timesteps and tiles of width 16, and FDTD2D runs a problem of size 128 by 128 with 2 timesteps and tiles of width 4 by 4.…”
Section: Applicationsmentioning
confidence: 99%